Fiscal Decentralization, Good Governance and Local Economic Development in councils in Ngoketunjia Division, Cameroon - Fagha, Munjah Vitalis (Archives of Business Research, 2024)
Abstract Dissatisfaction about the form of the state in Cameroon led to the putting in place of law No. 2019/024 of December 2019 instituting the General Code of Regional and Local Authorities, envisioned to improve local governance and impact local economic development. This, it was hoped will limit the interference of the central government in the management of regional and local affairs. Contrary to this theoretical supposition, there is still apparent strong centralization of financial powers by the central government in Cameroon. The rapport between the central government and the lower levels of government is rather that of command and obey relationship. Consequently, fiscal decentralization that is likely to promote good governance and engender local economic development at both regional and local levels appears to be rather an instrument of control for the central government, raising a concern as to the link existing between fiscal decentralization, good governance and local economic development in councils in Ngoketunjia Division. Employing largely a quantitative approach and within the prism of survey research design, guided by the efficiency theory of local government, findings revealed that fiscal decentralization, good governance and the transfer of revenue assignments and expenditure responsibilities following the enactment of the decentralization code on local economic development in councils in Ngoketunjia division has achieved little local economic development, established statistically by a calculated chi square value which stood at 152.14 as opposed to table value 26.217, leading to the rejection of the alternative hypothesis while the null hypothesis was accepted. It was discovered again that, there is no significant link between fiscal decentralization, good governance and local economic development in Councils in Ngoketunjia Division, shown in the computation of chi square test that stood at 130.8, disparate to table value of 26.217. The outcome was the rejection of the alternative hypotheses and acceptance of the null hypothesis. The paper concludes that, in Cameroon and particularly in the councils in Ngoketunjia division, there is tight de-concentration power rather than fiscal decentralization and good governance, suggesting that, the impact of fiscal decentralization and good governance on local economic development in councils in Ngoketunjia division is simply an ideological construct yearning for effective implementation. Keywords: Fiscal Decentralisation, Good Governance, Local Economic Development, Decentralisation, Local Government